Sadranan Sebagai Bentuk Komunikasi Sosial - Hanun Wuryansari; Puji Lestari; Isbandi Sutrisno (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2014)
This research aims to identify the form of social communication in Sadranan ceremony tradition. Research method that uses for collecting data are qualitative descriptive with interview, observation, documentation and study literature. Data are analyzed using validity techniqueas triangulated-source. This research investigates pre-procession, performance and post-ceremonial of Sadranan. Values that presented in Sadranan ceremonial consist of kinship and mutual-help. The discussion is refers to Theory of Symbol, Cultural Theory, and Interaksionisme simbolis by. Conclusions that can be drawn are Sadranan ceremony, as a symbol has dual concept namely general concept as grave-pilgrimage and specific concept as thankfulness to God the One, welcoming Ramadhan, praying forgiveness for ancestor spirit, and maintaining social relation during Sadranan procession. Sadranan ceremony is one of communication element with urges people to meet and communicate. Sadranan ceremony as native costum remain performed till nowadays and develops which represent native custom particularly Karangturi village. It is also concluded that Sadranan ceremony has be through value modification which inserted with Islam principles.